2014
DOI: 10.1111/1471-0528.13118
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and pelvic girdle pain: a follow‐up study of 10 603 women 18 months after delivery

Abstract: Objective To study the associations of patterns and duration of breastfeeding with the persistence of pelvic girdle pain 18 months after delivery.Design Longitudinal population study.Setting Norway, for the period 1999-2011.Population A follow-up of 10 603 women with singleton deliveries in the Norwegian Mother and Child Cohort Study who reported pelvic girdle pain at 0-3 months postpartum.Methods Data were obtained by four self-administered questionnaires and linked to the Medical Birth Registry of Norway.Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A weakness of our study was that the sample size (in the women with PGP, n = 37) is not of sufficient number to rule out a type II error for the small difference in the primary and secondary outcome variables measured. Moreover, BMI, breastfeeding and emotional distress shown to influence the prognosis of PGP, were not included [ 16 , 24 , 25 , 35 ]. It may also be the case that predictors of PGP outcome are not fixed at specific time points (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A weakness of our study was that the sample size (in the women with PGP, n = 37) is not of sufficient number to rule out a type II error for the small difference in the primary and secondary outcome variables measured. Moreover, BMI, breastfeeding and emotional distress shown to influence the prognosis of PGP, were not included [ 16 , 24 , 25 , 35 ]. It may also be the case that predictors of PGP outcome are not fixed at specific time points (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Items showing no association with PGP at 2, 6, and 11 years after pregnancy were the total number of pregnancies, number of children, birth weight, and gender of the last born baby16 ) . Breastfeeding patterns at 5 months after delivery were not associated with persistence of PGP19 ) . Sitting position during breastfeeding was not associated with persistent postpartum PGP (OR: 1.5, 95% CI: 0.9–2.8)26 ) .…”
Section: Resultsmentioning
confidence: 87%
“…1. Flow chart of the study selection process.. All 22 studies were longitudinal, prospective cohort studies, cross-sectional studies, or case studies8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29 ) . The sample sizes ranged from 3620 ) to 10,6033 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding have several health bene ts for mother and baby. A follow-up study found that breastfeeding had bene cial effect on the recovery process of pelvic girdle pain after childbirth [32].…”
Section: Discussionmentioning
confidence: 99%